Triple helix synergy: Segregation of household hazardous and toxic waste in the Banjar Serasan community - Patriani, Ira; Zhan, Fuzy Firda; Afhiani, Syarifah Nurma; Apriyani, Eka; Padilah, Ahirul Habib; Suhamsyah, Akhmad Mirza; Gusvira, Emelita; Fitri, Desita Syawlina (Journal of Community Service and Empowerment, 2023)
As the human population increases, the need for daily living also increases. This has an impact on increasing the amount of waste produced, including hazardous and toxic waste. However, public awareness of managing hazardous and toxic waste is still low. Many people do not separate hazardous and toxic waste from other waste due to a lack of awareness and knowledge about hazardous and toxic waste management. Based on this background, this Community Service activity was carried out to socialize the segregation of household hazardous and toxic waste in the Banjar Serasan community. The method used in this activity is using a case study approach, pre-test, lecture, discussion, and post-test. Before the presentation of material from the resource persons, there were still participants who did not know what household hazardous and toxic waste was, its types, and how to manage it, namely 8 out of 18 participants. After the material was given, all participants managed to understand what hazardous and toxic waste was and ways to apply the management and application of reduce, reuse, and recycle in handling it. Through this activity, it is hoped that it can support increased education for the public regarding the issue of hazardous and toxic waste that is relevant to the SDGs points including point 13, namely climate action.